2017
DOI: 10.1134/s0006297917070021
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and some aspects of the biological activity of mitochondria-targeted antioxidants

Abstract: This review summarizes for the first time data on the design and synthesis of biologically active compounds of a new generation - mitochondria-targeted antioxidants, which are natural (or synthetic) p-benzoquinones conjugated via a lipophilic linker with (triphenyl)phosphonium or ammonium cations with delocalized charge. It also describes the synthesis of mitochondria-targeted antioxidants - uncouplers of oxidative phosphorylation - based on fluorescent dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Skulachev (SkQ1) antioxidants are similar to MitoQ, however they involve the use of conjugated mitochondrial targeted motifs, like rhodamine and TPP, to plastiquinone [171] .…”
Section: Toxin Induced Models Of Admentioning
confidence: 99%
“…Skulachev (SkQ1) antioxidants are similar to MitoQ, however they involve the use of conjugated mitochondrial targeted motifs, like rhodamine and TPP, to plastiquinone [171] .…”
Section: Toxin Induced Models Of Admentioning
confidence: 99%
“…Previously, we have shown that plastoquinone as an antioxidative part of the conjugate demonstrates wide protective effects [ 16 ] and later it has been elucidated that neuroprotective properties of mitochondria-targeted antioxidants were determined not only by the quinone part but also the penetrating part itself [ 17 ]. Plastoquinone is present in natural photosynthetic systems, being an electron carrier in electron transport chains of chloroplasts and cyanobacteria reported to possess a strong antioxidative property [ 18 , 19 ]. The therapeutic efficiency of mitochondria-targeted antioxidants has been demonstrated in animal models of oxidative stress-related pathologies of brain [ 17 , 20 , 21 , 22 ], kidneys [ 22 , 23 , 24 , 25 , 26 ], and heart [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the new cationic uncoupler—rhodamine-19 butyl ether (C4R1) effectively accumulates in mitochondria to a certain concentration, without disturbing their vital functions. In experiments on rats—models of ischemic stroke, it was shown that the introduction of C4R1 after a reversible violation of cerebral circulation significantly reduced the scale of brain damage to animals and related neurological disorders (Korshunova et al, 2017; Lyamzaev et al, 2018; Silachev et al, 2018; Genrikhs et al, 2019). It should be noted that preventing the production of oxygen radicals in mitochondria is a fundamental principle in the fight against many diseases.…”
Section: Discussionmentioning
confidence: 99%